The Relationship Between Sociodemographics and Environmental Values Across Seven European Countries - Sargisson, Rebecca J.; De Groot, Judith I. M.; Steg, Linda (Frontiers in Psychology, 2020)
Given the importance of environmental values (altruistic, biospheric, and egoistic) to pro-environmental behaviour, it would be useful to segment the population – an approach known as market segmentation – to tailor pro-environmental messages more effectively. Sociodemographic variables are popular targets for segmentation, as such variables are often knowable in the absence of more nuanced information about individuals. However, evidence for the relationship between sociodemographics and environmental values is sparse, and contradictory. We examined the extent to which popular sociodemographic variables (gender, age, income, education, urbanization level, and political orientation) were predictive of environmental values for 11,820 participants across seven European countries. Overall, sociodemographics were hardly related to environmental values. Only gender and political orientation were weakly but significantly related to environmental values, whereby men and right-wingers showed weaker altruistic and biospheric, and stronger egoistic, values than women and left-wingers. We conclude that sociodemographic variables cannot be considered a suitable proxy for environmental values, and thus that behaviour-change campaigns might be more impactful when focused on alternative segmentation strategies in relation to environmental aims.